Development of a method of providing ergonomics of a web-interface for customers of a virtual instrument-making enterprise with limited physical capabilities - Sobchak, Andrii; Kovshar, Nataliiе; Lutai, Liudmyla; Fedorenko, Mykola; Fedorenko, Mykola; Dmytriieva, Oksana (Eastern-European Journal of Enterprise Technologies, 2021)
A method has been developed and implemented to ensure the ergonomics of using the Web interface for customers of a virtual instrument-making enterprise with limited capabilities through the use of expert systems. The essence of this method is to supplement the dialog component of the Information and Analytical Portal (IAP) with a specialized shell of the expert system (ES), which, being filled with knowledge about the limited capabilities of users caused by various pathologies, makes it possible to adapt the interface in the dialogue to the capabilities of a particular user. implementations of this solution method are fully consistent with the results obtained using the principles of interface improvement. However, due to the use in this synthesis method of various approaches to the technology of expert systems development, additional opportunities open up in solving the problem of providing the convenience of using the interface for customers with limited capabilities. When using the proposed method, it becomes possible to simplify the procedure of interaction "man-machine", to solve the problems of people with disabilities, to increase the volume of consumers who have access to advanced information technologies. These facts, confirmed by the results of numerical modeling, showed the effectiveness of the presented method and an individual approach to users with disabilities. The software implementation of the logical-linguistic hierarchical model on the example of “strong myopia” with the help of the production shell ES is proposed and substantiated. As the initial data, information about hardware was used, the use of which, in appropriate cases, will make it possible to increase the ergonomics of the IAP for users with disabilities.